2023
DOI: 10.47127/ijtmr.v6i2.171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Use on the Academic Performance of Students of Private Tertiary Institutions in Ghana: The Valley View University Perspective

Abstract: This paper examines the impact of social media use on the academic performance of students in private tertiary institutions in Ghana. The descriptive survey design was adopted for the study. The Valley View University, Oyibi Campus, Accra, was used as a case study. The population for the study was 2,172. The simple random sampling technique was used to sample 388 students. The questionnaire was used to solicit data for the study. 388 copies of the questionnaire were administered to the students. However, 362 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The results were supported by what Akporhonor and Akpojotor (2016), Ameyaw et al (2016) and Ternenge and Kashimana (2019) found in their research studies. They revealed that users faced challenges in accessing electronic resources in libraries and they attributed the challenges to the unreliable power supply and poor internet connectivity.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results were supported by what Akporhonor and Akpojotor (2016), Ameyaw et al (2016) and Ternenge and Kashimana (2019) found in their research studies. They revealed that users faced challenges in accessing electronic resources in libraries and they attributed the challenges to the unreliable power supply and poor internet connectivity.…”
Section: Resultssupporting
confidence: 81%
“…According to Kwafoa et al (2014), due to the importance and usefulness of electronic resources, CARLIGH pays an average of 25 0000 US Dollars as a subscription fee to enable affiliated institutions to have unlimited access to selected scholarly electronic resources for their information need at a subsidy. Moreover, studies such as Akporhonor and Akpojotor (2016), Ameyaw et al (2016), Ternenge and Kashimana (2019), found that unreliable power supply and poor internet connectivity are some of the challenges users face in accessing electronic resources in libraries.…”
Section: Literature Reviewmentioning
confidence: 99%